2020
DOI: 10.3389/fcell.2020.567682
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of TGF-β Signaling in Cerebrovascular Diseases

Abstract: Cerebrovascular diseases are one of the leading causes of death worldwide, however, little progress has been made in preventing or treating these diseases to date. The transforming growth factor-β (TGF-β) signaling pathway plays crucial and highly complicated roles in cerebrovascular development and homeostasis, and dysregulated TGF-β signaling contributes to cerebrovascular diseases. In this review, we provide an updated overview of the functional role of TGF-β signaling in the cerebrovascular system under ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 158 publications
0
25
0
Order By: Relevance
“…Further, previous studies showed that TGFβ1 mRNA and that of its induced pro-fibrotic target genes is upregulated in Dutch-type CAA and is associated with increased CAA severity (Moursel et al, 2018;Zhang & Yang, 2020). TGFβ1 has been reported to induce vascular fibrosis, mediate brain endothelial dysfunction, increased BBB permeability through downstream molecules such as FSP1 (S100A4) and Vim, and is associated with perivascular accumulation of ApoE (Moursel et al, 2018;Derada Troletti et al 2016;Derada Troletti et al 2019;Ueberham et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Further, previous studies showed that TGFβ1 mRNA and that of its induced pro-fibrotic target genes is upregulated in Dutch-type CAA and is associated with increased CAA severity (Moursel et al, 2018;Zhang & Yang, 2020). TGFβ1 has been reported to induce vascular fibrosis, mediate brain endothelial dysfunction, increased BBB permeability through downstream molecules such as FSP1 (S100A4) and Vim, and is associated with perivascular accumulation of ApoE (Moursel et al, 2018;Derada Troletti et al 2016;Derada Troletti et al 2019;Ueberham et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of TGF-β1 was predicted in the cortex of rTg-DI and rTg-DI/SHR-SP rats ( Figure 12A ). We have previously shown increases in TGF-β1 mRNA expression and IPA indicated activation of TGF-β1 in 12 M rTg-DI rats, and other studies have linked upregulation of TGF-β1 mRNA in Dutch-type CAA to increased CAA severity ( Moursel et al, 2018 ; Zhang and Yang, 2020 ; Zhu et al, 2020 ; Schrader et al, 2021 ). Interestingly, it has been reported that TGF-β1 deficiency in the neurovascular unit increases BBB permeability and that TGF-β1 released from astrocytes promotes BBB integrity ( Garcia et al, 2004 ; Derada Troletti et al, 2016 ).…”
Section: Discussionmentioning
confidence: 72%
“…Interestingly, experiments on HUVECs demonstrated that shear stress activates TGF-β, leading to downstream activation of Krüppel-Like Factor 2 (KLF2) and eNOS in an ALK5 dependent manner ( Walshe et al, 2013 ; Figure 2 ). Moreover, TGF-β malfunction through the SMAD signaling pathway has been linked to diverse cerebrovascular diseases related to aberrant endothelial cell proliferation (including HHT), as reviewed by Zhang and Yang (2020) .…”
Section: Mechanisms Of Vessel Enlargementmentioning
confidence: 99%